Coronary Stenosis Physiology and Novel Technologies - Pravda, Nili Schamroth (Rambam Maimonides Med J, 2020)
An accurate functional assessment of coronary artery stenosis is pivotal in the management and clinical outcomes of patients. The hemodynamic relevance of coronary artery stenoses can be assessed using coronary flow surrogates, namely fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR). This review provides an overview of these indexes, their clinical relevance, as well as a review of the literature supporting their use. It also reviews novel image-based FFR (e.g. FFRangio), the evidence showing the accuracy of this technique when compared to conventional wire-based techniques, as well as the clinical implications of non-invasive coronary artery stenosis functional assessments.